The Relationship between Financial Technology, Lifestyle, and Financial Behavior: A Case Study of Generation Z in Sorong, Southwest Papua - Maulin Adinda; Andhiny Syafridha Jumsar; Nurul Hidayah (IECON: International Economics and Business Conference, 2024)
The rise of cashless transactions has brought transformative changes to financial behaviors, particularly among Generation Z. Financial Technology (Fintech) plays a pivotal role in this shift, significantly enhancing the speed, convenience, and reliability of purchasing, selling, and payment processes. These advancements have had a profound impact on how individuals, especially younger generations, manage their financial activities. Despite this, previous studies exploring the relationship between Fintech adoption, lifestyle factors, and the financial behaviors of Generation Z have shown mixed and sometimes contradictory results. This study focuses on assessing the influence of Fintech and lifestyle factors on the financial behaviors of Generation Z in Sorong City. Using a purposive sampling method, 397 respondents were selected to represent the target population. Quantitative data analysis was performed through multiple linear regression analysis, utilizing SPSS software to examine the relationships between variables. The findings reveal that Fintech exerts a statistically significant influence on the financial behaviors of Generation Z, underscoring its critical role in shaping their financial decision-making processes. In contrast, lifestyle factors were found to have no significant impact on financial behaviors. These results highlight the dominance of technology in influencing financial practices, suggesting that efforts to enhance financial behaviors should prioritize Fintech adoption and literacy over lifestyle adjustments.